Pelatihan dan Praktik Penyelenggaraan Fardhu Kifayah Dosen, Karyawan, dan Mahasiswa di Masjid Amirulhaq Balikpapan - Firman Firman; Sugianto Sugianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
This service is about training and practice in carrying out fardhu kifayah carried out at the Amirulhaq Campus Mosque, Balikpapan University. The service was carried out to answer the anxiety faced by the community, namely that attention to the care of corpses was becoming increasingly low, so it seemed as if the responsibility for caring for corpses was handed over only to the fardhu kifayah community. The focus of the problem in this service is to guide and train participants in the process of administering and managing people who have died. The training aims to provide participants with knowledge and insight into how to handle corpses. Furthermore, it motivates so that after this training participants become involved if someone dies in their environment, especially their own family. This activity begins with the delivery of the activity stages from the beginning to the end of the training. The activity stages begin with participant registration and are then divided into groups of both male and female participants. Next, the implementation method provides material about handling people who have died and matters related to death. Then it continues with the practice of cutting the shroud, washing, shrouding, and praying the body. The results of this activity show that the participants gained experience in the form of knowledge so that they could know and understand both the concept and practice of implementing fardhu kifayah.